Duel in the sun [videorecording (DVD)] - Vidor, King, 1894-1982; Jones, Jennifer, 1919-2009; Cotten, Joseph, 1905-1994; Peck, Gregory, 1916-2003; Busch, Niven, 1903-1991 (Kino Lorber, 2017)
Orphaned after her father is hanged for killing his wife and her lover, Pearl, who is half Native American, goes to live with distant cousins where she experiences prejudice and forbidden love.